2021
DOI: 10.1186/s12887-021-02681-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of cardiorespiratory fitness standards for working memory using receiver operating curves in 15-year-old adolescents

Abstract: Background Working memory performance is associated with better academic achievements in children and adolescents, and it is positively related to CRF. However, what level of cardiorespiratory fitness (CRF) discriminates higher working memory performance is not known. The purpose of this study was to identify CRF thresholds linked to working memory in adolescents. Methods Data of 141 adolescents (53.2 % girls) were collected (14.9 years) from a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…This relates to previous findings on how gender can influence one's SDL efficacy: adolescent girls (compared to boys of the same age) in general have a greater willingness to put effort into learning (Schweder and Raufelder, 2019). Considering that developmental maturation of the cognitive control takes longer for boys (the impact of the testosterone on cortical advancement) compared to girls who are found to be less influenced by the cerebral structures changes in adolescence (Delevich et al, 2018;Weber et al, 2021). Female students aged 14-16 years have significantly higher SDL readiness (than the same age males), while for males, a level of SDL readiness similar to females is predicted from 21 years onwards (Reio and Davis, 2005).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This relates to previous findings on how gender can influence one's SDL efficacy: adolescent girls (compared to boys of the same age) in general have a greater willingness to put effort into learning (Schweder and Raufelder, 2019). Considering that developmental maturation of the cognitive control takes longer for boys (the impact of the testosterone on cortical advancement) compared to girls who are found to be less influenced by the cerebral structures changes in adolescence (Delevich et al, 2018;Weber et al, 2021). Female students aged 14-16 years have significantly higher SDL readiness (than the same age males), while for males, a level of SDL readiness similar to females is predicted from 21 years onwards (Reio and Davis, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…In a review of recent research on the topic, Schweder and Raufelder (2019) have shown that multiple studies have found gender differences related to learning: adolescent girls (compared to boys of the same age) in general have greater willingness to put effort into learning, while boys evince fewer control strategies compared to girls. The latter is found to be related to the fact that, in terms of development, the maturation of the cognitive control advancement takes longer for boys than for girls (Weber et al, 2021). Girls are thought to suffer less from the influence on particular cerebral structure changes caused by the impact of testosterone on the cortical thickness and gray matter volume in the frontal lobes of the brain (Delevich et al, 2018).…”
Section: Self-directed Learning and Gender Differencesmentioning
confidence: 97%
See 3 more Smart Citations